Attack on Titan : before the fall. 9 - Suzukaze, Ryo (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2016)
"The anti-establishment dissidents' attempted rebellion runs up against harsh reality when the Military Police hit them hard almost before it starts, thanks to Xavi's infiltration of their ranks. Meanwhile, Kuklo uses his new Device to spring to Sharle's aid. But unbeknownst to him, his oldest nemesis will be waiting in the wings" -- Page [4] of cover.